Out-of-plane and in-plane ferroelectricity of atom-thick two-dimensional InSe. (29th June 2021) - Hu, Haowen; Wang, Huaipeng; Sun, Yilin; Li, Jiawei; Wei, Jinliang; Xie, Dan; Zhu, Hongwei
Abstract: Two-dimensional (2D) ferroelectric materials are promising substitutes of three-dimensional perovskite based ferroelectric ceramic materials. Yet most studies have been focused on the construction of non-centrosymmetric 2D van der Waals materials and only a few are constructed experimentally. Herein, we experimentally demonstrate the co-existence of voltage-tunable out-of-plane (OOP) and in-plane (IP) ferroelectricity in few-layer InSe prepared by a solution-processable method and fabricate ferroelectric semiconductor channel transistors. The reversible polarization can initiate instant switch of resistance with high ON/OFF ratios and a comparable subthreshold swing of 160 mV/dec under gate modulation. The origins of such unique OOP and IP ferroelectricity of the centrosymmetric structure are theoretically analyzed.